Forage seed production and trade as a pathway out of poverty in the smallholder sector: Lessons from the Zimbabwe Crop Livestock Integration for Food Security (ZimCLIFS) project - Chakoma, Irenie; Gwiriri, Lovemore C.; Manyawu, Godfrey J.; Dube, Sikhalazo; Shumba, M.; Gora, A. (National Inquiry Services Center, 2016)
The major challenge to adoption of improved forage technologies in the smallholder farming sector is poor accessibility to seed of improved cultivars. Since 2012, the Zimbabwe Crop Livestock Integration for Improved Food Security (ZimCLIFS) project set out to address such challenges through research-for-development initiatives. The main objective was to demonstrate the potential viability of a pasture seed business using a lead farmer approach, farmer-to-farmer technology dissemination, innovation platforms and field demonstrations. Snapshot surveys were used to map forage seed distribution pathways within and outside project areas. Total land area planted to forages from the 2012/13 to 2014/15 seasons increased by 147% from 14.6 ha. In 2013, Mucuna pruriens (mucuna), Lablab purpureus (lablab) and Vigna unguiculata (cowpea) seed produced was 2 250 kg, 120 kg and 4 450 kg, respectively, and by the third season, total yield increased by 163%. Seed diffusion was within and beyond project boundaries, with mucuna (67%) and lablab (43%) seed produced in the 2013/14 season being distributed outside the project area. Highest amounts received by some farmers were US$800 and US$750 for lablab and mucuna, respectively. It was concluded that there is scope to develop formal pasture seed businesses to increase rural industrialisation and provide a pathway out of poverty in the smallholder sector.